The Return of Doi Menre' Ba‘da Duhul in Bugis Marriage Law, South Konawe: Islamic Education and Sociology of Islamic Law Perspective - Mansur, Mansur; Ihsan, Muh.; Diab, Ashadi L.; Nurfaidah, Sitti; Darlis, Syamsul (El-Usrah: Jurnal Hukum Keluarga, 2024)
Doi Menre' (gift money) can be returned after the divorce takes place even though husband and wife relations have previously occurred (ba‘da duhul). This research examines the practice of returning doi menre' (gifted money) ba‘da duhul, the social dynamics that influence it, as well as sociology of Islamic Law and Islamic Education perspectives regarding the practice of returning doi menre' (gifted money) ba‘da duhul for the Bugis community in South Konawe Regency, Southeast Sulawesi. This qualitative research employs a socio-empirical approach, including interviews with those who have returned doi menre' (gifted money) ba‘da duhul's, traditional leaders, community leaders, and religious leaders. The results of the research revealed that the return of doi menre' ba‘da duhul's was practiced in two stages, namely the pre-wedding verbal agreement stage and the stage of returning the doi menre' (gifted money). Three social dynamics influence the return of doi menre' ba‘da duhul's, namely; there was an oral agreement before the marriage took place, no solution was found to the marriage problems, and following the habits of some Bugis people in resolving divorce cases. Islamic education in the tradition of returning doi menre' ba‘da duhul in Bugis marriage law plays a foundation in forming principled, moral, fair in building a household, and contribute positively to social life. Sociological studies of Islamic law view that the practice of returning doi menre' (gifted money) is a managed system in the actions of the Bugis community which combines customary law and Islamic law in resolving divorce cases. In the end, research can participate in developing an assessment of the struggle between customary law and Islamic law in resolving marriage cases in Islamic communities.